INFECTIOUS MONONUCLEOSIS: CLINICAL PRESENTATION, DIAGNOSIS, AND TREATMENT METHODS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Infectious mononucleosis (IM), caused by the Epstein-Barr virus (EBV), is a globally prevalent viral disease characterized by fever, lymphadenopathy, and pharyngitis. This article provides a comprehensive review of IM, including its etiology, epidemiology, clinical manifestations, diagnostic methods, management strategies, and potential complications. Special attention is given to the disease's pathogenesis and its association with long-term complications, such as malignancies. Emphasis is placed on the importance of accurate diagnosis and supportive care, while exploring future preventive measures, including vaccine development.